The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.15560/17.6.1493
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of Planorbinae (Heterobranchia, Hygrophila, Planorbidae) from northwestern Argentina

Abstract: The family Planorbidae comprises freshwater gastropods with planispiral, spiral and limpet-shaped shells. Subfamily Planorbinae sensu stricto, has a richness of almost 300 species, with some of the main genera being Biomphalaria Preston, 1910 and Drepanotrema Fischer & Crosse, 1880. Some Biomphalaria species are of concern to human health as they are intermediate hosts of blood flukes in Latin America. In Argentina, the family Planorbidae is represented by 15 species in four genera. In Northern Argenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The shell morphology of Anisus vortex, four Bulinus species, Biomphalaria tenagophila, and Gyraulus sp. is taken by Skipp and Ablett [29], Zhang et al [14], Ovando and Marchi [51], Sitnikova et al [52], respectively. The shell morphology of Planorbella duryi is downloaded from the web of Australian Freshwater Molluscs (https://keys.lucidcentral.org/keys/v3/freshwater_molluscs/, accessed on 29 December 2023) [53].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The shell morphology of Anisus vortex, four Bulinus species, Biomphalaria tenagophila, and Gyraulus sp. is taken by Skipp and Ablett [29], Zhang et al [14], Ovando and Marchi [51], Sitnikova et al [52], respectively. The shell morphology of Planorbella duryi is downloaded from the web of Australian Freshwater Molluscs (https://keys.lucidcentral.org/keys/v3/freshwater_molluscs/, accessed on 29 December 2023) [53].…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“… Bithyniidae Alocinma sp., Bithynia sp., Parafossarulus sp. CS , OF , OV Naveen and Singh ( 2019 ), Ovando and Marchi ( 2021 ), Palasio et al ( 2018 ), Saadi et al ( 2020 ), Saito ( 2022 ), Schultz et al ( 2018 ); Adema et al ( 2017 ), Anderson and Enabulele ( 2021 ), Hailegebriel et al ( 2020 ), Llanwarne and Helmby ( 2021 ), Rey et al ( 2021 ), Siles-Lucas et al ( 2021 ) Physidae Physa sp. AC Planorbidae Biomphalaria sp.…”
Section: The Biology Of Snails In Relation To Parasitic Disease Trans...mentioning
confidence: 99%
“…The WHO has reported that approximately 770 million people are at risk of schistosomiasis, and it is spread over more than 78 countries in Africa, Asia, and Latin America, especially in poor communities (WHO 2022 ). Biomphalaria , Lanistes , Planorbarius , Neotricula , Oncomelania , Robertsiella , and Melanoides species of snails are responsible for acting as intermediate hosts for these blood flukes (Ovando and Marchi 2021 ; Saito 2022 ). The infective stage is either schistosomula or cercarial penetration on the skin (Anderson and Enabulele 2021 ; Li et al 2021 ; Limpanont et al 2020 ).…”
Section: Snail-transmitted Parasitic Diseases In Animals and Humansmentioning
confidence: 99%
See 1 more Smart Citation